Experimental study on steel tank model using shaking table = Badania eksperymentalne modelu zbiornika stalowego na stole sejsmicznym - Burkacki, Daniel; Jankowski, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Cylindrical steel tanks are very popular structures used for storage of products of chemical and petroleum industries. Earthquakes are the most dangerous and also the most unpredictable dynamic loads acting on such structures. On the other hand, mining tremors are usually considered to be less severe due to lower acceleration levels observed.
Keywords: stalowy zbiornik walcowy; model zbiornika; niezawodność; obciążenia dynamiczne; trzęsienie ziemi; stół wibracyjny; badania eksperymentalne; cylindrical steel tank; shaking table; earthquake; mining tremor; sweep-sine tests